Preparation method of nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor

In the preparation of the precursor of the positive electrode material of sodium ion battery, the co-precipitation technology of nickel manganese titanium zinc is used to solve the problems of uneven element distribution and precipitation of zinc elements, which improves the tap density and cycle stability of the battery and extends the The service life of the battery.

CN119191389AInactive Publication Date: 2024-12-27HENAN KELONG NEW ENERGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411708707.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The elements in the precursors of the existing sodium ion battery positive electrode material are uneven, resulting in low tap density, poor battery energy density and cycling performance, and zinc elements are prone to precipitation, resulting in sulfate residue, affecting battery capacity and stability.

Method used

The preparation method of the precursor of the positive electrode material of nickel manganese titanium zinc sodium ion battery is adopted. By preparing nickel manganese mixed salt solution, titanium complex solution and zinc ammonia complex solution at room temperature, and co-precipitation reaction is carried out in the reactor to control the mole The pH value is used to isolate oxygen with protective gas, solid-liquid separation, washing and drying to obtain a uniformly distributed precursor.

Benefits of technology

The uniform distribution of elements in the precursor is achieved, the tap density and particle consistency are improved, the energy density and cycle stability of sodium ion batteries are improved, the trivalent manganese content is reduced, the phase change degree is reduced, and the battery is extended. cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191389A_ABST
    Figure CN119191389A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor. The specific process comprises the following steps: simultaneously adding a nickel-manganese mixed salt solution, a titanium complexing solution, a zinc-ammonia complexing solution and an alkali solution into a reaction kettle containing a kettle bottom solution through four feeding pipes, and carrying out a co-precipitation reaction to prepare a nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor; the method can realize simultaneous precipitation of four metal ions of Ni < 2 + >, Mn < 2 + >, Ti < 4 + > and Zn < 2 + >, elements in the obtained precursor are uniformly distributed, the molar ratio completely meets a target value, and the nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor prepared by the method is uniform in morphology, good in consistency, high in tap density, uniform in element distribution and free of segregation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of positive electrode material precursors for sodium ion batteries, and specifically relates to a method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery. Background Art

[0002] As an emerging battery technology, sodium-ion batteries have gradually attracted great attention from the industry in recent years. With abundant sodium resources, low costs and stable electrochemical performance, they are gradually becoming an important candidate to replace traditional lithium-ion batteries. They have been applied in energy storage, low-speed electric vehicles and other fields. In addition, with the continuous advancement of technology and the reduction of costs, the application of sodium-ion batteries in electric vehicles, power tools and other fields will also gradually unfold. Layered transition metal oxide sodium batteries are currently the fastest-growing sodium-ion battery technology, with a relatively clear path to industrialization. Compared with other sodium-ion battery technology routes, layered oxide sodium batteries have more advantages in energy density, cycle life, safety and stability.

[0003] Sodium ion cathode material is an important component of sodium ion battery, and its performance directly affects the electrochemical performance and cycle life of sodium ion battery. Therefore, the selection of cathode material precursor has a decisive influence on the performance of sodium ion battery. However, due to the large ionic radius and slow kinetic rate of sodium ions, the stress of the main lattice of the material changes greatly during the embedding reaction, and the precipitation coefficients of titanium and nickel and manganese hydroxides are quite different, which leads to the inability of the elements to co-precipitate evenly during the precipitation process, resulting in segregation of particles. In addition, in the precipitation reaction, the chelating ability of chelating agents such as ammonia water on zinc is weak, which makes it easy for zinc to precipitate in advance during the reaction, resulting in element segregation. The segregation of elements in the precursor not only affects the uniformity of element distribution of the precursor, but also affects the tap density of the precursor, making the tap density of the fired material often low, affecting the energy density of the sodium ion battery. At the same time, it will make the residual sulfate in the precursor difficult to wash. The content of residual sulfate in the precursor is high, and the residual sulfate will remain in the positive electrode material after sintering, resulting in a decrease in battery capacity, which also seriously affects the volume energy density and cycle performance of the positive electrode material.

[0004] Patent document CN116969520A discloses a sodium electric precursor and its preparation method and application. The preparation process includes the following steps: mixing nickel salt, manganese salt and iron salt with a solvent to obtain solution A, mixing copper salt, complexing agent and solvent to obtain solution B, mixing one or more of lithium salt, zinc salt, titanium salt or magnesium salt with solvent to obtain solution C; injecting alkali solution, ammonia water and solution A into the bottom liquid in parallel to carry out a one-step coprecipitation reaction, injecting ammonia water, alkali solution and solution B in parallel to carry out a two-step coprecipitation reaction; injecting precipitant solution and solution C in parallel to carry out a three-step coprecipitation reaction to obtain a sodium electric precursor. This method prepares a high entropy superlattice sodium electric precursor by a step-by-step coprecipitation method. However, the preparation process of this patent does not involve the relevant record of preparing a sodium electric precursor by a single nickel-cobalt-zinc-titanium coprecipitation reaction to improve its tap density, and in the third step coprecipitation reaction, zinc salt and titanium salt are coprecipitated in the form of a conventional zinc salt aqueous solution under the joint action of a precipitant and a complexing agent. Patent document CN118572084A discloses a core-shell type sodium ion battery positive electrode material and its preparation method and application, wherein the positive electrode material comprises a nickel-iron-manganese core and a zinc-magnesium co-doped shell, and the preparation process comprises: mixing nickel salt, iron salt, manganese salt and deionized water to obtain a first metal salt solution; mixing zinc salt, magnesium salt and deionized water to obtain a second metal salt solution; adding the first metal salt solution, precipitant solution and complexing agent solution to the bottom liquid in parallel to perform a coprecipitation reaction to obtain a nickel-iron-manganese core precursor; replacing the first metal salt solution with the second metal salt solution, and continuing the coprecipitation reaction to obtain a mixed core-shell type sodium ion battery precursor. In this patent, zinc salt is in the form of a conventional zinc salt aqueous solution under the joint action of a precipitant and a complexing agent to perform a coprecipitation reaction to form a shell coating structure, and the process only involves a coprecipitation reaction of zinc salt and magnesium salt for secondary precipitation. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery. 2+ , Mn 2+ 、Ti 4+ 、Zn 2+ The four metal ions are precipitated simultaneously, and the elements in the obtained precursor are evenly distributed, and the molar ratio completely meets the target value. In addition, the nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor prepared by this method has uniform morphology, good consistency, high tap density and uniform element distribution without segregation.

[0006] After research, it was found that at room temperature, the solubility product of Ni(OH)2 is Ksp=4.8×10 -16 , the solubility product of Mn(OH)2 is Ksp=2.4×10 -14 , the solubility product of Zn(OH)2 is Ksp=1.8×10 -14 , the solubility product of Ti(OH)2 is Ksp=1×10-29 However, due to the large difference in the solubility product between Ti and Ni, Mn, and Zn, it is difficult to achieve uniform co-precipitation. The density of the co-precipitated product is low, the primary particles are uneven, and zinc and nickel and manganese are prepared into a mixed solution for precipitation. The precursor particle structure is unstable and particles are prone to adhesion and primary particle shedding. The tap density is low, and the post-processing of the material is more difficult.

[0007] In order to ensure that the molar ratio meets the requirements and the precursor has a stable secondary particle morphology and a uniform primary particle morphology as well as good physical and chemical indicators such as density, specific surface area and sodium-sulfur impurity content, the present invention adopts the following technical solution: A method for preparing a nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor, the specific steps of which are: Step S1: According to the chemical formula Ni x Mn y Ti z Zn (1-x-y-z) The molar ratios of Ni, Mn, Ti and Zn in (OH)2 are respectively used to prepare nickel-manganese mixed salt solution, titanium complex solution and zinc-ammonia complex solution, where 0.2≤x<0.5, 0.1≤y<1, 0 <z≤0.15,0<x+y+z<1; Step S2: adding the nickel-manganese mixed salt solution, titanium complex solution, zinc-ammonia complex solution and alkaline solution obtained in step S1 into the reactor containing the bottom solution through four feeding tubes to carry out a co-precipitation reaction, and introducing a protective gas to isolate oxygen during the reaction; Step S3: The coprecipitated product obtained in step S2 is subjected to solid-liquid separation, washing, drying and screening to obtain the target product, a nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor, wherein the tap density TD of the sodium ion battery positive electrode material precursor is greater than 1.30 g / cm 3 , the specific surface area BET is 10~35m 2 / g, particle size D50 is 3.0~6.5μm.

[0008] It is further defined that the nickel salt in the nickel-manganese mixed salt solution in step S1 is one or more of nickel sulfate, nickel chloride or nickel nitrate, and the manganese salt is one or more of manganese sulfate or manganese chloride; the titanium salt in the titanium complex solution is one or more of TiCl4, Ti(SO4)2 or Ti(NO3)4, and the complexing agent in the titanium complex solution is one of citric acid, tartaric acid or glucose; the zinc salt in the zinc-ammonia complex solution is one or more of ZnCl2, ZnSO4 or Zn(NO3)2, and the complexing agent in the zinc-ammonia complex solution is ammonia water; and the alkaline solution is sodium hydroxide solution.

[0009] It is further defined that the total concentration of nickel and manganese ions in the nickel-manganese mixed salt solution in step S2 is 150~500g / L, and the flow rate of the nickel-manganese mixed salt solution is 3.6~6L / h; the concentration of titanium ions in the titanium complex solution is 20~100g / L, and the flow rate of the titanium complex solution is 0.5~2L / h; the concentration of zinc ions in the zinc-ammine complex solution is 10~25g / L, the concentration of ammonium ions in the zinc-ammine complex solution is 10~40g / L, and the flow rate of the zinc-ammine complex solution is 0.5~2L / h; the concentration of the alkaline solution is 4~10mol / L, and the pH value of the reaction system is controlled to be 10.50~12.10 by adjusting the flow rate of the alkaline solution.

[0010] It is further defined that the kettle bottom solution in step S2 is a mixed solution of ammonia water, liquid alkali and pure water, the concentration of ammonium ions in the kettle bottom solution is 3~12g / L, the pH value of the kettle bottom solution is 10.50~12.10, and the volume of the kettle bottom solution is 30%~80% of the effective volume of the reactor.

[0011] It is further defined that the coprecipitation reaction temperature in step S2 is 35-70° C., the precipitation reaction time is 30-80 h, and the stirring speed of the precipitation reaction is 400-800 r / min.

[0012] It is further defined that the protective gas in step S2 is nitrogen, and the flow rate of the protective gas is 5-50 L / min.

[0013] It is further defined that the washing process in step S3 is to wash the coprecipitated product until the pH of the eluent is less than 10, and the drying process is to place the coprecipitated product in a constant temperature oven and heat it to 110-120° C. for drying for 9-14 hours.

[0014] Compared with the prior art, the present invention has the following advantages and beneficial effects: the present invention realizes ultra-high capacity (175 mAh / g) of sodium battery under high voltage (2-4.4 V) through uniform co-precipitation of titanium, zinc and nickel-manganese, and the positive electrode material after firing has uniform primary particles and high tap density, thereby improving the compaction density of the positive electrode material and greatly improving the energy density of the sodium ion battery; at the same time, the addition of titanium can effectively improve the average valence state of the Mn element, reduce the content of trivalent manganese, weaken the Jahn-Taylor effect of trivalent manganese, reduce the degree of phase change, improve the stability of the positive electrode material, greatly improve the cycle stability performance of the sodium battery material, solve the problems of irreversible phase change and structural collapse caused by high voltage conditions and poor battery cycle stability performance, thereby greatly improving the cycle service life of the sodium ion battery; and the preparation process of the present invention is simple, and the doping amount of Ti and Zn in the prepared sodium ion battery positive electrode material precursor is relatively high. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1This is an SEM image of the sodium ion battery positive electrode material precursor prepared in Example 1.

[0016] Figure 2 This is an SEM image of the sodium ion battery positive electrode material precursor prepared in Example 1.

[0017] Figure 3 This is the SEM image of the sodium ion battery positive electrode material precursor prepared in Comparative Example 1.

[0018] Figure 4 This is the SEM image of the sodium ion battery positive electrode material precursor prepared in Comparative Example 1. DETAILED DESCRIPTION

[0019] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example 1

[0020] (1) Nickel sulfate and manganese sulfate are dissolved in water to prepare a nickel-manganese mixed salt solution with a total ion concentration of Ni and Mn of 2.0 mol / L.

[0021] Zinc sulfate was prepared into a zinc sulfate solution with a zinc ion concentration of 0.35 mol / L at room temperature, and 6 mol / L ammonia water was slowly added thereto with stirring. Zinc hydroxide was first produced during the preparation process, and ammonia water was continuously added until the precipitate completely disappeared, thereby obtaining a zinc ammonia complex solution with a zinc ion concentration of 18 g / L and an ammonium ion concentration of 31.5 g / L.

[0022] Titanium sulfate was dissolved in dilute sulfuric acid to prepare a titanium sulfate solution with a titanium ion concentration of 400 g / L, and a citric acid solution with a concentration of 400 g / L was slowly added thereto to prepare a titanium complex solution with a titanium ion concentration of 90 g / L.

[0023] A 6 mol / L sodium hydroxide solution was prepared as a precipitant, and a 6 mol / L ammonia solution was prepared as a complexing agent for preparing the bottom solution of the kettle and a complexing agent for preparing the zinc-ammonia complex solution.

[0024] (2) Add 60 L of pure water to a reactor with an effective volume of 100 L. The temperature is controlled at 60°C. The ammonium ion concentration of the bottom solution of the reactor is adjusted to 5.5 g / L with an ammonia solution. The pH of the bottom solution of the reactor is adjusted to 11.90 with a sodium hydroxide solution.

[0025] The prepared nickel-manganese mixed salt solution, zinc-ammonia complex solution, titanium complex solution and sodium hydroxide solution are added into the reactor in parallel for co-precipitation reaction, and the flow rate of each solution is controlled according to the molar ratio of nickel, manganese, titanium and zinc of 4:4:1:1; the stirring speed is controlled to be 700r / min during the reaction, wherein the flow rate of the nickel-manganese mixed salt solution is 4.8L / h; during the co-precipitation reaction, the pH value of the reaction system is controlled at 11.50 by adjusting the flow rate of the sodium hydroxide solution, the reaction temperature is 60°C, the nitrogen gas bubbled into the reactor is controlled by a float flowmeter to maintain 30L / min, the oxygen content is always kept <1.0% during the entire reaction process, the reaction atmosphere is kept in a completely non-oxidizing state, and the co-precipitation reaction time is 70h.

[0026] (3) The slurry obtained by the reaction was separated into solid and liquid by a plate and frame filter press, and the solid phase was collected. The material separated by the filter press was washed with a 6wt% sodium hydroxide solution, and then washed with pure water until the pH was <10. The material was dried in a constant temperature drying oven at 115°C for 12 hours until the moisture content reached 3000ppm, and finally Ni 0.40 Mn 0.40 Ti 0.10 Zn 0.10 (OH)2 precursor.

[0027] Test the prepared precursor: The Ni 0.40 Mn 0.40 Ti 0.10 Zn 0.10 The (OH)2 precursor was tested by tungsten scanning electron microscopy. Figure 1~2 This is the SEM image.

[0028] The particle size D of the precursor prepared in this example was measured by Malvern particle size tester. 50 The surface area is 5.2 μm, and the specific surface area is 16.78 m 2 / g, and its tap density is 1.59g / cm 3 , Na content is 190ppm, S content is 2342ppm.

[0029] Comparative Example 1 (1) Nickel sulfate, manganese sulfate, titanium sulfate and zinc sulfate are dissolved in a dilute sulfuric acid aqueous solution to prepare a nickel-manganese-titanium-zinc mixed salt solution with a total ion concentration of Ni, Mn, Ti and Zn of 2.5 mol / L.

[0030] Prepare 6 mol / L sodium hydroxide solution as a precipitant, and prepare 6 mol / L ammonia solution as a complexing agent for preparing the bottom solution.

[0031] (2) Add 60 L of pure water to a reactor with an effective volume of 100 L. The temperature is controlled at 60°C. The ammonium ion concentration of the bottom solution of the reactor is adjusted to 5.5 g / L with an ammonia solution. The pH of the bottom solution of the reactor is adjusted to 11.90 with a sodium hydroxide solution.

[0032] The prepared nickel-manganese-titanium-zinc mixed salt solution, sodium hydroxide solution and ammonia solution are respectively added into the reactor in parallel for co-precipitation reaction, and the flow rate of each solution is controlled according to the molar ratio of nickel, manganese, titanium and zinc of 4:4:1:1; during the reaction, the stirring speed is controlled at 700r / min, and the flow rate of the nickel-manganese-titanium-zinc mixed salt solution is 4.8L / h; during the co-precipitation reaction, the pH value of the reaction system is controlled at 11.50 by adjusting the flow rate of the sodium hydroxide solution, the reaction temperature is 60°C, the nitrogen gas bubbled into the reactor is controlled by a float flowmeter to maintain 25L / min, the oxygen content is maintained at <1% during the entire reaction process, the reaction atmosphere is maintained in a completely non-oxidizing state, and the reaction time is 70h.

[0033] (3) The slurry obtained by the reaction was separated into solid and liquid by a plate and frame filter press, and the solid phase was collected. The material separated by the filter press was washed with a 6wt% sodium hydroxide solution, and then washed with pure water until the pH was <10. The material was dried in a constant temperature drying oven at 115°C for 12 hours until the moisture content reached 3000ppm, and finally Ni 0.40 Mn 0.40 Ti 0.10 Zn 0.10 (OH)2 precursor.

[0034] Test the prepared precursor: The Ni 0.40 Mn 0.40 Ti 0.10 Zn 0.10 The (OH)2 precursor was tested by tungsten scanning electron microscopy. Figure 3~4 This is the SEM image.

[0035] The particle size D of the precursor prepared in this comparative example was measured by Malvern particle size tester. 50 The surface area is 5.150 μm, and the specific surface area is 22.65 m 2 / g, and its tap density is 1.15g / cm 3 , Na content is 190ppm, S content is 3690ppm.

[0036] Comparing the precursors prepared in Example 1 with those prepared in Comparative Example 1, the particle sizes D 50 The specifications are all 5.2 μm. In Comparative Example 1, titanium and zinc were not pre-complexed. Figure 3~4It can be seen that the precursor primary particles are uneven in size, with obvious morphological differences, and there are micropowders. The thickness consistency of the primary particle lath is poor, and the tap density is 1.15g / cm 3 , BET is 22.65m 2 / g, which proves that its tap density is low, the product particles are relatively empty, and the sulfur content is relatively high. The sulfur impurities cannot be washed off by the same washing process, which proves that more by-product basic zinc sulfate is produced under this process. The sulfate group structure in basic zinc sulfate is stable and cannot be removed by conventional liquid alkali washing. In Example 1, zinc and titanium are pre-complexed and pumped in parallel and co-precipitated simultaneously. The pre-complexation effectively alleviates the problem of large differences in the solubility products of various metal elements, reduces the difference in the deposition rate of each element, and allows the crystals to be uniformly and effectively precipitated and stacked. The final precursor particles are densely stacked, the primary particles are tightly stacked, the precursor particles have good consistency, and the tap density is 1.59g / cm 3 , BET is 16.78m 2 / g, which has a higher tap density and a smaller specific surface area than that of comparative example 1, indicating that the metal ion salt solution that has been pre-complexed can effectively increase the tap density of the precursor particles, reduce surface voids, and enhance their structural stability.

[0037] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery, characterized in that The specific steps are: Step S1: According to the chemical formula Ni x Mn y Ti z Zn (1-x-y-z) The molar ratios of Ni, Mn, Ti and Zn in (OH)2 are used to prepare nickel-manganese mixed salt solution, titanium complex solution and zinc-ammonia complex solution, respectively, where 0.2≤x<0.5, 0.1≤y<1, 0 <z≤0.15,0<x+y+z<1; Step S2: adding the nickel-manganese mixed salt solution, titanium complex solution, zinc-ammonia complex solution and alkaline solution obtained in step S1 into the reactor containing the bottom solution through four feeding tubes to carry out a co-precipitation reaction, and introducing a protective gas to isolate oxygen during the reaction; Step S3: The coprecipitated product obtained in step S2 is subjected to solid-liquid separation, washing, drying and screening to obtain the target product, a nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor, wherein the tap density TD of the sodium ion battery positive electrode material precursor is greater than 1.30 g / cm 3 , the specific surface area BET is 10~35m 2 / g, particle size D50 is 3.0~6.5μm.

2. The method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery according to claim 1, characterized in that: The nickel salt in the nickel-manganese mixed salt solution in step S1 is one or more of nickel sulfate, nickel chloride or nickel nitrate, and the manganese salt is one or more of manganese sulfate or manganese chloride; the titanium salt in the titanium complex solution is one or more of TiCl4, Ti(SO4)2 or Ti(NO3)4, and the complexing agent in the titanium complex solution is one of citric acid, tartaric acid or glucose; the zinc salt in the zinc-ammine complex solution is one or more of ZnCl2, ZnSO4 or Zn(NO3)2, and the complexing agent in the zinc-ammine complex solution is ammonia water; the alkaline solution is sodium hydroxide solution.

3. The method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery according to claim 1, characterized in that: The total concentration of nickel and manganese ions in the nickel-manganese mixed salt solution in step S2 is 150-500 g / L, and the flow rate of the nickel-manganese mixed salt solution is 3.6-6 L / h; the concentration of titanium ions in the titanium complex solution is 20-100 g / L, and the flow rate of the titanium complex solution is 0.5-2 L / h; the concentration of zinc ions in the zinc-ammine complex solution is 10-25 g / L, the concentration of ammonium ions in the zinc-ammine complex solution is 10-40 g / L, and the flow rate of the zinc-ammine complex solution is 0.5-2 L / h; the concentration of the alkaline solution is 4-10 mol / L, and the pH value of the reaction system is controlled to be 10.50-12.10 by adjusting the flow rate of the alkaline solution.

4. The method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery according to claim 1, characterized in that: The kettle bottom solution in step S2 is a mixed solution of ammonia water, liquid alkali and pure water, the concentration of ammonium ions in the kettle bottom solution is 3-12 g / L, the pH value of the kettle bottom solution is 10.50-12.10, and the volume of the kettle bottom solution is 30%-80% of the effective volume of the reactor.

5. The method for preparing a nickel-manganese-titanium-zinc sodium ion battery positive electrode material precursor according to claim 1, characterized in that: The coprecipitation reaction temperature in step S2 is 35-70° C., the precipitation reaction time is 30-80 h, and the stirring speed of the precipitation reaction is 400-800 r / min.

6. The method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery according to claim 1, characterized in that: The protective gas in step S2 is nitrogen, and the flow rate of the protective gas is 5-50 L / min.

7. The method for preparing a positive electrode material precursor for a nickel-manganese-titanium-zinc sodium ion battery according to claim 1, characterized in that: The washing process in step S3 is to wash the coprecipitated product until the pH of the eluent is less than 10, and the drying process is to place the coprecipitated product in a constant temperature oven and heat it to 110-120° C. for drying for 9-14 hours.

Citation Information

Patent Citations

  • Preparation method of titanium-doped lithium ion positive electrode material precursor

    CN109768275A

  • Doped lithium nickel manganese oxide positive material and preparation method for precursor material of the same

    CN109860585A

  • Five-membered precursor material and preparation method and application thereof

    CN112209450A

  • Zinc-titanium co-doped O3 type sodium battery positive electrode material as well as preparation method and application thereof

    CN118782783A

  • Zinc-containing sodium ion battery positive electrode material precursor and preparation method thereof

    CN119018945A